2001
DOI: 10.1089/15230860152542925
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation of Zinc-Binding Cysteine Residues in Transcription Factor Proteins

Abstract: Recent results on the oxidation of cysteine residues that bind zinc in transcription factors and their analogous peptides and in related proteins and model systems are reviewed. Two classes of oxidants, the transition metals and dioxygen, hydrogen peroxide, and related species, are considered, and the role of metal ions in suppressing or enhancing Cys oxidation is a major focus. Cysteines in the zinc-bound structures of transcription factors are less susceptible to oxidation than in the metal-free form, and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
57
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(58 citation statements)
references
References 82 publications
1
57
0
Order By: Relevance
“…After treatment with H 2 O 2 , DTT was able to partially (about 50%) restore the DNA complex formation of VDR/RXR (Fig. 2C) (21), or even thiosulfinate (Cys-SO-S-Cys) (52). Among the amino acids present in proteins only cysteines are modified by NO ⅐ (53), while the other reactive species used in this study are able to modify additional amino acids in proteins also, e.g.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…After treatment with H 2 O 2 , DTT was able to partially (about 50%) restore the DNA complex formation of VDR/RXR (Fig. 2C) (21), or even thiosulfinate (Cys-SO-S-Cys) (52). Among the amino acids present in proteins only cysteines are modified by NO ⅐ (53), while the other reactive species used in this study are able to modify additional amino acids in proteins also, e.g.…”
Section: Discussionmentioning
confidence: 78%
“…by alkylating compounds (for reviews see Refs. 20,21). The question therefore arises, whether the reaction of NO ⅐ with zinc fingers may have a special role, different from the reaction with other reactive species generated during inflammatory reactions.…”
mentioning
confidence: 99%
“…10 It is known that oxidation of zinc finger motif by reactive oxygen species can cause zinc release, leading to dysfunction and degradation of zinc finger transcription factors. 29,30 Clinical data from alcoholic patients has shown that the imbalance between cell death and proliferation in the liver correlates inversely with glutathione levels and directly with lipid peroxidation. 19 Our previous report also showed that zinc supplementation 922 Kang et al AJP April 2008, Vol.…”
Section: Discussionmentioning
confidence: 99%
“…11,12,24 -28 Zinc is a critical component in the zinc finger motif of zinc finger transcription factors, and the release of zinc from the zinc finger motif leads to a loss of the DNA binding ability of zinc finger transcription factors. 29,30 Hepatocyte nuclear factor-4␣ (HNF-4␣), a zinc finger protein, is a liver-enriched transcription factor, 31 and has been reported to bind the promoters of more than 1000 genes involved in most aspects of hepatocyte function including cell proliferation. 32 Both human and animal data demonstrate that HNF-4␣ is essential for maintaining liver gene expression and a decrease in HNF-␣ correlates with the severity of liver damage.…”
mentioning
confidence: 99%
“…We propose that a highly oxidized Cys-110 forms a thiolsulfinate with the thiol group of Cys-132 (Fig. 10A) (33).…”
Section: Molecular Interactions Responsible For the Redox Modulation mentioning
confidence: 96%